Laporan Kasus: Manajemen Anestesi Umum dengan Intubasi Nasotrakeal pada Fraktur Maxilla Dextra dan Fraktur Dentoalveolar - Alicia Sarijuwita; Subhan Yudihart; Yohanes Firmansyah (Universitas Malahayati Lampung, 2026)
ABSTRACT Maxillofacial trauma, particularly maxillary fractures, poses significant challenges in anesthetic management due to potential airway compromise, bleeding, and anatomical distortion. Adequate airway control is critical to ensure patient safety while allowing optimal surgical access during maxillofacial procedures. Nasotracheal intubation is commonly employed in such cases; however, its use requires careful evaluation to avoid complications, especially in patients with midface trauma. We report a case of a 17-year-old male patient who presented following a motorcycle traffic accident with complaints of facial pain, right periorbital swelling, epistaxis, and intraoral bleeding. Computed tomography imaging revealed a right maxillary fracture extending to the nasal bone accompanied by a dentoalveolar fracture. The patient was scheduled for open reduction and internal fixation (ORIF). General anesthesia was administered using nasotracheal intubation with controlled ventilation. Intraoperative monitoring demonstrated stable hemodynamic and respiratory parameters throughout the approximately two-hour surgical procedure, with no anesthetic-related complications observed. Maxillary fractures, particularly those involving the midfacial region, are associated with an increased risk of airway obstruction and bleeding, making airway management a major concern in anesthetic practice. Nasotracheal intubation provides unobstructed access to the oral cavity and is advantageous for maxillofacial surgery when contraindications such as skull base fractures are excluded. This case highlights the importance of comprehensive preoperative airway assessment, appropriate anesthetic planning, and close intraoperative monitoring to ensure safe perioperative management in patients with maxillofacial trauma. This case emphasizes that nasotracheal intubation under general anesthesia is a safe and effective airway management strategy in selected patients with maxillary and dentoalveolar fractures. Early assessment and multidisciplinary coordination play a vital role in optimizing perioperative outcomes and minimizing complications. Keywords: Maxillofacial Trauma, Maxillary Fracture, Dentoalveolar Fracture, Nasotracheal Intubation, Airway Management, General Anesthesia. ABSTRAK Trauma maksilofasial, khususnya fraktur maksila, merupakan tantangan tersendiri dalam praktik anestesi karena berpotensi menyebabkan gangguan jalan napas, perdarahan, serta perubahan anatomi yang dapat menyulitkan pengelolaan jalan napas. Pengamanan jalan napas yang adekuat sangat krusial untuk menjamin keselamatan pasien sekaligus memungkinkan akses bedah yang optimal selama prosedur maksilofasial. Kami melaporkan suatu kasus pasien laki-laki berusia 17 tahun yang datang pascakecelakaan lalu lintas sepeda motor dengan keluhan nyeri wajah, pembengkakan periorbital kanan, epistaksis, dan perdarahan intraoral. Evaluasi klinis dan pemeriksaan tomografi terkomputasi menunjukkan fraktur maksila dextra yang meluas hingga os nasal disertai fraktur dentoalveolar. Pasien direncanakan menjalani tindakan open reduction and internal fixation (ORIF) dan dilakukan anestesi umum dengan teknik intubasi nasotrakeal serta ventilasi terkontrol. Selama prosedur pembedahan yang berlangsung sekitar dua jam, parameter hemodinamik dan respirasi pasien terpantau stabil tanpa ditemukannya komplikasi terkait anestesi. Fraktur maksila, terutama yang melibatkan regio midfasial, memiliki risiko tinggi terhadap obstruksi jalan napas dan perdarahan, sehingga manajemen jalan napas menjadi aspek krusial dalam tatalaksana anestesi. Intubasi nasotrakeal memberikan keuntungan berupa akses bebas ke rongga mulut dan lapangan operasi yang lebih optimal, serta dapat digunakan secara aman apabila kontraindikasi seperti fraktur dasar tengkorak telah disingkirkan melalui evaluasi praoperatif yang menyeluruh. Kasus ini menegaskan pentingnya penilaian jalan napas yang komprehensif, perencanaan anestesi yang tepat, serta pemantauan intraoperatif yang ketat dalam menangani pasien dengan trauma maksilofasial. Dengan pendekatan tersebut, intubasi nasotrakeal pada anestesi umum dapat menjadi pilihan yang aman dan efektif pada pembedahan fraktur maksila dan dentoalveolar untuk mencapai luaran perioperatif yang optimal. Kata Kunci: Trauma Maksilofasial, Fraktur Maksila, Fraktur Dentoalveolar, Intubasi Nasotrakeal, Manajemen Jalan Napas, Anestesi Umum.